Morphometry of Jatropha curcas L. seeds as a function of provenance - Aquino, Noelle Farias de; Ajala, Michelle Cristina; Dranski, João Alexandre; Ignácio, Vanessa Leonardo; Malavasi, Marlene de Matos; Malavasi, Ubirajara Contro (Revista de Ciências Agroveterinárias, 2009)
The objective of this study was to correlate unidimensional measurements with biomass of Jatropha curcas seeds from Pernambuco (PE), Minas Gerais (MG) and Mato Grosso do Sul (MS) provenances. Results showed statiscatical differences among linear measurements as well as seed biomass. The small seed diameter measured from the rafis and perpendicular to seed length yielded the highest correlation coefficients for all three provenances (0.72 PE; 0.66 MG; e 0.44 MS), followed by those from seed length (0.66 PE; 0.65 MG e 0.33 MS), while the large seed diameter yielded the least significant correlation coefficients with seed biomass (0.44 PE; 0.37 MG e 0.20 MS). The best calculated models were M = -1.177 + 0.102 dme + 0.051 c for the PE seed provenance, M = -1.271 + 0.143 dme + 0.040 c for the MG seed provenance and M = -0.845 + 0. 111 dme + 0.028 c for the MS seed provenance.